Peran Penampilan dalam Mempengaruhi Kesuksesan Karir Selebgram di Era Digital pada Akun Instgram Malaikha Dayanara - Andini Azzahra Putri; Moch. Ichda Asyarin Halau Lailin; Ratna Ningrum Zusyana Dewi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Visual-based social media platforms like Instagram have given rise to the phenomenon of beauty privilege, which refers to the social and professional advantages gained by individuals with attractive appearances. This study aims to examine the influence of appearance indicators within the beauty privilege variable on the career success of the influencer Malaikha Dayanara. The research uses a quantitative method with a survey approach. Data were collected through an online questionnaire filled out by 100 active followers of Malaikha’s Instagram account, using purposive sampling. Data analysis was conducted through validity testing, reliability testing, and partial t-test using statistical software. The results indicate that appearance indicators significantly influence the perception of career success, particularly in terms of increasing audience trust, personal branding, and attractiveness to brand collaboration opportunities. Physical appearance has proven to be a dominant factor in shaping a professional image and influencing public engagement with an influencer. These findings emphasize the crucial role of visual elements in building career success in the digital era. Visual appeal is not just about aesthetics but is an integral part of an effective communication strategy within the social media industry. Influencers with attractive appearances tend to have greater opportunities to expand their audience and attract brand attention. This shows that appearance plays a significant role in not only supporting digital success but also influencing the perception of professionalism and the ability to establish connections with the audience. Thus, physical appearance has become an essential element in creating a personal image that can influence career success, especially in a world increasingly dominated by visual-based platforms like Instagram. These findings offer insights into how appearance has become a strategic factor in achieving career success in the digital age.